Human DNA Ligases: A Comprehensive New Look for Cancer Therapy. Issue 3 (19th August 2013) - Singh, Deependra Kumar; Krishna, Shagun; Chandra, Sharat; Shameem, Mohammad; Deshmukh, Amit Laxmikant; Banerjee, Dibyendu
Abstract Living organisms belonging to all three domains of life, viz., eubacteria, archaeabacteria, and eukaryotes encode one or more DNA ligases. DNA ligases are indispensable in various DNA repair and replication processes and a deficiency or an inhibition of their activity can lead to accumulation of DNA damage and strand breaks. DNA damage, specially strand breaks at unsustainable levels can lead to replication block and/or cell death. DNA ligases as potential anticancer targets have been realized only recently. There is enough rationale to suggest that ligases have a tremendous potential for novel therapeutics including anticancer and antibacterial therapy, specially when the world is facing acute problems of drug resistance and chemotherapy failure, with an immediate need for new therapeutic targets. Here, we review the current state of the art in the development of human ligase inhibitors, their structures, molecular mechanisms, physiological effects, and their potential in future cancer therapy. Citing examples, we focus on strategies for improving the activity and specificity of existing and novel inhibitors by using structure‐based rational approaches. In the end, we describe potential new sites on the ligase I protein that can be targeted for the development of novel inhibitors. This is the first comprehensive review to compile all known human ligase inhibitors and to provide a rationale for the further development of ligase inhibitors for cancer therapy.